Peningkatan Aksesibilitas Bandar Udara Internasional Sultan Aji Muhammad Sulaiman Sepinggan Dengan Integrasi Antarmoda - Charmandri Rifqi Wiky Putra; Khairunnisa Adhar; Arief Hidayat; Dwiana Novianti Tufail; Srirahadita Pamungkas (COMPACT: Spatial Development Journal, 2025)
Sultan Aji Muhammad Sulaiman (SAMS) Sepinggan International Airport is one of the main transportation hubs for air travel in the Kalimantan region, particularly in the city of Balikpapan. SAMS Sepinggan International Airport is also among the busiest airports in Kalimantan. However, this situation has not yet become a central focus in the provision of adequate public transportation and mobility infrastructure. The high volume of passenger movement at SAMS Airport has the potential to contribute to increased traffic congestion, primarily due to the heavy reliance on private motor vehicles. Therefore, accessibility in the form of intermodal transportation integration is needed. Intermodal integration refers to efforts to develop cities, regions, or areas by integrating and/or connecting various types of transportation modes. It aims to achieve regional integration by improving accessibility, connectivity, and spatial cohesion through the connection of public transportation networks that are linked and integrated. This study employs qualitative methods including regulatory compliance analysis, mode preference analysis using the Analytic Hierarchy Process (AHP), and strategy formulation using SWOT analysis. Field findings indicate that the public desires transportation that is affordable, easily accessible, and well-integrated. Hence, coordination among transportation mode operators and improvements in service quality are necessary. Keywords : Airport, Intermodal Integration, Accessibility, Regulatory Compliance, AHP, SWOT